Determination of heavy metals in water bodies from the Regional Conservation Area Wetlands of Ventanilla-Callao, Peru - Fajardo Vidal, Narda (2017)
Heavy metals are often found as contaminants in the water. Accordingly, the current study was conducted to determine heavy metals (Hg, Cd, Pb, As) in water bodies from the Regional Conservation Area Wetlands of Ventanilla by the method of Inductively Coupled Plasma (ICP). Water samples were collected at 17 sampling stations for three monitoring periods for the analysis of four variables of the physico-chemical quality of the water bodies. The presence of these elements in water are important for environmental and health of human communities associated with water bodies. Some metals are quickly trapped by sediments, so its presence in the water column is indicative of recent contamination. The physicochemical characteristics found were compared with the proposed concentration limits of the Peruvian law of 2008 and 2015. In the case of heavy metals, lead, arsenic and mercury have higher values so that their potential sources are discussed.